(untitled) (Research, Society and Development, 2022)
Health risk management is the process that organizes, plans, controls and directs resources to minimize or control health risks within the institution. Risks in diagnostic imaging services are manageable, and avoidable, but there is no specific tool for risk management and patient safety. To develop software for health risk management in the diagnostic imaging service. Applied research on technological development, carried out in three stages: integrative literature review, online Delphi stage, and software construction. Quality Diagnosis software is a technology that identifies, analyzes, evaluates, treats, and monitors process failures and adverse events in diagnostic imaging services effectively with the execution of preventive, and corrective actions identified during root cause investigations. The software contributed to the implementation of the quality management of the Diagnostic Imaging Accreditation Program, aiming to disseminate the patient safety culture, and ensure quality care for all patients.